Antara Potensi dan Kendala Dalam Pengembangan Pariwisata di Sumatera Barat - Ferniza, Henny (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
The potential of tourism in West Sumatra continues to squirm. By having natural attractions (Lake, Valley, Mountains, Coast, Sea) also has a wide range of cultures that accompanied the various attractions and specific local knowledge. However, with the myriad of potentials and with a number of marketing strategies that have been carried out, West Sumatra tourism to flourish and far behind other regions such as Bali, Yogyakarta, Bandung, even North Sumatra. Of course there are obstacles in the development of tourism. To that end, in addition to reviewing the aspects that become obstacles for tourism development of West Sumatra, more concretely also examined aspects of the constraints in the tourist area of Lake Above and Below Lake which is one of the attractions in West Sumatra. This study used mixed methods (Mixed Method) with sequential exploratory strategy. The analytical method used is the Delphi method which is supported by the identification of constraints through the mass media, deskirptif analysis of qualitative and descriptive statistical analysis. The study shows that the main obstacle aspects of tourism development of West Sumatra is the mindset aspect of society, aspects of planning, financing support aspect. Another aspect is the economic society, marketing and infrastructure support. In contrast to the constraints of development of tourist areas of Lake Above and Below Lake, the results showed the obstacles in the form of people who think that mindset, tourism is less promising as a source of income, while the farm will get pengasilan great. The different thing is revealed when analyzing public perception of the response. It turned out that people do not know what exactly are the benefits of tourism, the public does not know which part they should play an active role, which means that people do not know its position in the tourism sector.